Comparison of serum F2 isoprostane levels in diabetic patients and diabetic patients infected with Burkholderia pseudomallei - Puthucheary, S.D.; Nathan, S.A. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
The oxidative stress theory proposes that severe sepsis leads to activation of neutrophils and macrophages which subsequently release reactive oxygen-free radicals that may result in lipid peroxidation of endothelial and epithelial cell membrane phospholipids. This chain reaction results in increased levels of isoprostanes, which are thought to contribute to much of the end-stage tissue damage seen in serious infections, such as melioidosis. We believe that this is the first report linking in vivo oxidative stress status and diabetic patients infected with B. pseudomallei.